Investigation of patient factors associated with the number of transfusions required during chemotherapy for high‐risk neuroblastoma. Issue 1 (1st July 2021) - Konno, Saori; Yanagisawa, Ryu; Kubota, Noriko; Ogiso, Yoshifumi; Nishimura, Noriyuki; Sakashita, Kazuo; Tozuka, Minoru
Abstract: Background: Blood transfusion is an important supportive care for high‐risk neuroblastoma. When the number of transfusions increases, transfusion‐associated adverse reactions may be more problematic. However, the factors determining the degree of myelosuppression and the number of transfusions during chemotherapy for high‐risk neuroblastoma remain unclear. Materials and Methods: We investigated patient factors determining the number of required transfusions in 15 high‐risk neuroblastoma patients who received five courses of chemotherapy. Clinical data, cytokine profile and colony‐forming assay with bone marrow samples at diagnosis were analysed. Results: The required number of transfusions of both platelets and erythrocytes decreased once in the second course and then increased as the course progressed. The variability among cases increased as the chemotherapy course progressed. In cases of low peripheral blood platelet count and lower fibrinogen level at diagnosis, the number of platelet transfusions was higher during chemotherapy. In contrast, there was a negative correlation between the forming ability of granulocyte–macrophage or erythroid colonies and the number of erythrocyte transfusions in the latter period. Conclusion: In the early stages of chemotherapy, bone marrow infiltration in neuroblastoma and/or coagulopathy complication may cause thrombocytopenia and requirement of platelet transfusion; conversely, in the later stages, the number of erythrocyte transfusions may be defined by the patient's inherent hematopoietic ability. These factors may be useful in predicting the required number of transfusions.